Dampak Persepsi dan Stigma Masyarakat tentang Covid-19 - Ernawati Umar; Dedeh Hamdiah (Faletehan Health Journal, 2021)
Covid-19 outbreak in Indonesia, dated November 15, 2020, infected 474.455 people who were tested positive, 398.636 people were recovered, while 15.393 peopledied. Negative perception and stigma attacked people related to Covid-19 and causedstress and depression whichcan reduce the immune system then cause death. This study aimedto determine the community perception andstigma about Covid 19 in Banten Province in 2020. This study was analytical descriptive and useda cross-sectional study approachto examine theperceptionand stigma of community who were infected bycovid 19. Thisstudy was conducted from June toNovember 2020 in Pandeglang Regency and Serang City. Thedata collection was by distributing questionnaires. The sampleswere 750 respondents. This study found a significant relationship between communityperception and community stigma, which influencesthe performance of health workersand the stress level of Covid-19 patientswith p value 0.00 for both. Negative perceptionand stigmamayimpact on the performance of health workers and cause depression in COVID-19 patients, which results on the decrease ofimmune system. Keywords: Covid-19, Community Perception, CommunityStigma